Fault kinematics and slip distribution of the 2023 M w 6.1 earthquake in Jishishan County (Gansu, China) based on InSAR observations - Shuyuan Yu; Shubi Zhang; Zhejun Li; Jiaji Luo; Yuanyuan Yang; Juan Ding (Earth, Planets and Space)
Abstract On December 18, 2023, a M w 6.1 earthquake occurred in Jishishan County, Linxia Prefecture, Gansu Province. This earthquake is the largest recorded since the establishment of seismic observations on the Lajishan fault zone along the northeastern edge of the Tibetan Plateau. This study utilizes Sentinel-1A satellite data to obtain the coseismic deformation field from ascending and descending tracks of the 2023 Jishishan earthquake, using this information to constrain the inversion of the earthquake's fault kinematic parameters and fault slip distribution characteristics. Finally, integrating the characteristics of Coulomb stress changes with regional tectonic background research results, we assess the seismic hazard of the region. The study indicates that the deformation field generated by this earthquake is oriented predominantly in the WNW direction, with the coseismic deformation from both ascending and descending tracks mostly exhibiting uplift. The maximum line-of-sight (LOS) displacement for the ascending track is approximately 6 cm, while for the descending track it is about 6.7 cm. The results of slip testing on the coseismic fault suggest that both east-dipping and west-dipping fault geometric models can adequately explain the parameters of the fault that caused this earthquake. Based on aftershock relocation and comprehensive analysis of the regional tectonic background, the study concludes that the rupture likely occurred on a northeast-dipping fault, potentially a concealed reverse fault with a WNW orientation located along the southern margin of Lajishan. Calculations of static Coulomb stress changes indicate that the occurrence of the 2023 Jishishan earthquake has increased the risk of future seismic events along segments of the WNW-oriented southern and northern margins of the Lajishan fault, as well as to the east of the epicenter along the Xiqinling northern fault and the Daotanghe-Linxia fault. Graphical Abstract